Brucellosis in livestock and wildlife: zoonotic diseases without pandemic potential in need of innovative one health approaches - Jacques Godfroid (BMC, 2017)
Abstract Human brucellosis remains the commonest zoonotic disease worldwide with more than 500 000 new cases annually. Understanding the biology of Brucella infections and the transmission patterns at the wildlife/livestock/human interface is of paramount importance before implementing any brucellosis control or eradication program in animals, even more so should interventions be justified within One Health. In addition to calling for transdisciplinary collaboration, One Health formally aims to conserve the environment and to promote the well-being of animals. In this opinion paper, the One Health approach of brucellosis is reviewed in the industrialized and the low and middle income countries, highlighting pitfalls and shortcomings of serological studies and discussing the role of urban and peri-urban farming for the re-emergence of brucellosis in the developing world. The role of wildlife as a potential reservoir is highlighted and different management strategies are discussed. Lastly, beyond its role in the control of brucellosis, the ethical dimension of culling wildlife to control disease emergence or spill-back of infections in livestock is discussed. Core transdisciplinary competencies such as values and ethics are critically important in guiding the development of One Health curricula and in continuing professional education, as they describe the knowledge, skills, and attitudes required to be effective. A conceptual framework needs to be developed from inception to knowledge translation. Importantly, transdisciplinary competencies should be developed as an adjunct to discipline-specific areas of expertise, not as a replacement. A profound understanding of the biology of infectious agents is and will always remain a pre-requisite for any sound One Health approach.